2008
DOI: 10.1016/s1472-6483(10)60600-1
|View full text |Cite
|
Sign up to set email alerts
|

Microchimeric fetal cells cluster at sites of tissue injury in lung decades after pregnancy

Abstract: Fetal cells trafficking into maternal blood during pregnancy engraft tissues and persist for decades in marrow and bone. While persistent fetal cells were initially implicated in autoimmune disease, animal studies suggest that microchimeric fetal cells play a broader role in response to tissue injury. This study investigated whether fetal cells participate in tissue repair after human pregnancy. Specimens were obtained from women undergoing surgery for suspected lung cancer. Y-fluorescence in-situ hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 33 publications
4
68
0
6
Order By: Relevance
“…Accordingly, fetal cell migration has been reported in other malignancies. 16,21,22 In breast carcinomas associated with pregnancies, 90% of specimens showed fetal cells in malignant tissue but never in benign mammary lesions developing also during pregnancy. 16 Fetal cell detection appears lower in our skin chemical murine model, but mice were not pregnant at the time of tumour development.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, fetal cell migration has been reported in other malignancies. 16,21,22 In breast carcinomas associated with pregnancies, 90% of specimens showed fetal cells in malignant tissue but never in benign mammary lesions developing also during pregnancy. 16 Fetal cell detection appears lower in our skin chemical murine model, but mice were not pregnant at the time of tumour development.…”
Section: Discussionmentioning
confidence: 99%
“…The method adopted for FISH was initially described by Johnson et al 42,43 As reported by O'Donoghue et al, 44 skin sections (5 µm) were processed in the usual way, then heat and enzyme pre-treated and fixed before hybridization. This technique was tested on normal skin, scarred and hypertrophic tissue, where the duration of heat enzyme pre-treatment was adjusted.…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
“…Slides were rinsed in tap water and dehydrated in 100% ethanol for 30 s. After being air-dried, the slides were mounted in DAPI (diamidino-2-phenyl-indole, Vector Laboratories), covered with 22 × 22mm coverslips, and sealed with nail varnish. 16,19,[42][43][44] Fluorescent Immunohistochemistry combined with FISH In order to identify the phenotype of microchimeric cells found in the tissue sections, Immunohistochemistry for markers of fetal wound healing was performed with Cytokeratin, Collagen I, III, Fibronectin, Transforming growth factor β1 (TGFβ1), and Transforming growth factor β3 (TGFβ3), was done on the same sections following FISH. (Table 6).…”
Section: Fluorescent Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…FMCs selectively home to damaged tissues where they are found in a higher frequency than in uninjured control tissues [6,7]. They can either be a part of the inflammatory infiltrate or integrated into the surrounding maternal tissue, displaying niche-appropriate phenotypes [4,8].…”
mentioning
confidence: 99%